2011
DOI: 10.1186/1753-6561-5-s2-s11
|View full text |Cite
|
Sign up to set email alerts
|

Inferring ethnicity from mitochondrial DNA sequence

Abstract: BackgroundThe assignment of DNA samples to coarse population groups can be a useful but difficult task. One such example is the inference of coarse ethnic groupings for forensic applications. Ethnicity plays an important role in forensic investigation and can be inferred with the help of genetic markers. Being maternally inherited, of high copy number, and robust persistence in degraded samples, mitochondrial DNA may be useful for inferring coarse ethnicity. In this study, we compare the performance of methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Several studies have indicated the feasibility of inferring the probable geographic origin of an individual from the sequence of hypervariable regions (HV) of the mitochondrial genome. These studies clearly demonstrate that the mitochondrial sequence alone does not determine one's ethnicity because it relates exclusively to maternal inheritance [2], [12], [13].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Several studies have indicated the feasibility of inferring the probable geographic origin of an individual from the sequence of hypervariable regions (HV) of the mitochondrial genome. These studies clearly demonstrate that the mitochondrial sequence alone does not determine one's ethnicity because it relates exclusively to maternal inheritance [2], [12], [13].…”
Section: Introductionmentioning
confidence: 85%
“…The analysis of both types of information, AIMs and mtDNA, could be strongly associated and, thereby, used to infer more accurately the ethnic origin of an individual [2], [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…MtDNA studies have been used to reconstruct the human demographic history as well as to infer the ancestry of individuals [5]. In this sense, the study of American human groups has awakened a growing interest because of their complexity and diversity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated the feasibility of inferring the probable geographic origin of an individual from the sequence of the hypervariable regions (HV) of mitochondrial genome. These studies clearly demonstrate that the mitochondrial sequence alone does not determine one's ethnicity, by presenting exclusively maternal inheritance 1,10 .…”
mentioning
confidence: 89%
“…However, in highly admixed populations, such as in Brazil, this personal information cannot provide the same robust estimative as in less diverse populations 1,2 .…”
mentioning
confidence: 99%